AGILE PRODUCT DEVELOPMENT: REQUIREMENTS PRIORITIZATION USING ANALYTICAL HIERARCHY PROCESS (AHP) DECISION MAKING WITHIN AGILE WAY OF WORKING IN DIGITAL BANKING LENDING PRODUCT - Reivan Yuliar H P, M
Insan Bank, as a company already adopt agile way of working to its project management. Agile is one of methods of way of working that become increasingly famous and being pursued by companies that are entering digitalization due to its feature which promote agility and adaptability to the current trend. Within project management there is a particular activity called product development that become the research subject of this paper. This is because there is increasing needs of the company to have efficient product development. As the research progressed, it is found that Requirement clarity is one of major factors during product development process which affect the efficiency. Requirement clarity includes the specifications, the scope, impacts, as well as the importance of the requirement. If requirement is unclear, the product development efficiency will decrease. It is hypothesized that prioritization of requirements will solve the issue and able to increase product development efficiency. Upon this hypothesis, as proposed solution, the author suggests the use of Analytical Hierarchy Process (AHP) as methods to create prioritization of the requirements. As the methods is part of Multi-Criteria Decision Making (MCDM), the methodology appears to be suitable to be used in the context of product development in Insan Banking. From the AHP methods proposed in this paper, the study shows that the AHP can be used to determine the prioritization of requirements, especially with ratings approach. The decision makers who are shown the simulation are showing optimistic view towards the use of AHP as it able to increase the efficiency of product development.